2016
DOI: 10.7759/cureus.895
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Multidisciplinary Case Conferences on Physician Decision Making: Breast Diagnostic Rounds

Abstract: Purpose: To evaluate the utility of multidisciplinary case conferences (MCCs) on physician decision making in benign and malignant breast disease management.Methods:  Patients with interesting or challenging diagnostic or management issues were discussed at biweekly diagnostic breast MCCs. Prior to discussion, a clinical summary and intended management plan prior to the MCC was presented. For each case, diagnostic images/histopathology were centrally reviewed after which group discussion achieved a management … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
26
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 21 publications
(28 citation statements)
references
References 27 publications
2
26
0
Order By: Relevance
“… 9 The proposed strategies for treating 41% of cases were reformed following the NCCN guidelines. 10 The TB had a significant effect on changing 40% of treatment plans and 60% of staging and assessment plans. 11 Another study demonstrated staging modifications or alterations of treatment plans in 60% of patients.…”
Section: Discussionmentioning
confidence: 99%
“… 9 The proposed strategies for treating 41% of cases were reformed following the NCCN guidelines. 10 The TB had a significant effect on changing 40% of treatment plans and 60% of staging and assessment plans. 11 Another study demonstrated staging modifications or alterations of treatment plans in 60% of patients.…”
Section: Discussionmentioning
confidence: 99%
“…A study in Taiwan that compared those receiving MDT treatment with those without found that MDT intervention significantly increased the breast cancer survival rate [ 100 ]. A population study from a region in Germany suggested there may be evidence of increased mortality if breast cancer patients do not receive guideline compatible treatment [ 101 ]. There are studies that report changes in treatment plans following MDT discussion.…”
Section: Supporting Evidence and Informationmentioning
confidence: 99%
“…The current literature provides evidence that MDTMs are achieving intended objectives [ 3 , 4 ]. MDTMs lead to significant changes in the way cancer patients are assessed and managed [ 1 , 5 ] and lead to improved outcomes [ 6 - 8 ]. But there are also indications to question the positive impact of MDTMs in oncology settings [ 9 ].…”
Section: Introductionmentioning
confidence: 99%